Pengembangan Masalah Geometri Bangun Ruang Berbasis Kearifan Lokal untuk Mengukur Kemampuan Berpikir Kritis - Muhammad Hendriyanto; Ismail, Ismail; Hartono, Sugi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop non-routine mathematics problems containing East Javanese local wisdom as a tool for measuring critical thinking in junior high school students in solid geometry. The context of local wisdom used included the Limas Trajumas Lawakan House, the Tenggerese house, and the Ketipung musical instrument. The method used was research and development (R&D) through the 4D model, but its implementation was limited to the third stage only. The development process included needs analysis, problem design based on critical thinking indicators, expert validation, revision, readability test, and practicality test. This study involved a lecturer and two mathematics teachers as validators, three students for the readability test, and 30 students and three mathematics teachers for the practicality test. The results showed that the designed problems successfully achieved a validity level of 87.72% (in the very valid category) and a practicality score of 89.89% (in the very practical category). In conclusion, the problems have met the instrument's eligibility standards so they can be implemented as an alternative contextual problem in geometry learning while evaluating junior high school students' critical thinking abilities. Keywords: Critical Thinking, Geometry, Local Wisdom, Problems